2001
DOI: 10.1007/s002390010165
|View full text |Cite
|
Sign up to set email alerts
|

Non-LTR Retrotransposons Encoding a Restriction Enzyme-Like Endonuclease in Vertebrates

Abstract: All autonomous non-long terminal repeat (non-LTR) retrotransposons reported to date in vertebrates encode an apurinic/apyrimidinic endonuclease-like enzyme necessary for target sequence cleavage and subsequent target-primed reverse transcription. We describe here vertebrate non-LTR retrotransposons encoding another type of endonuclease more related to type IIS restriction enzymes. Such retrotransposons have been detected until now only in trypanosomes, nematodes, and arthropods. The retrotransposon Rex6 was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 37 publications
1
91
0
Order By: Relevance
“…The highest homologies, 43 and 47%, respectively, were found to the retrotransposon element sushi of the pufferfish, Fugus rubripe. Further, ORF1 and ORF2 exhibited ϳ85% identity at the nucleotide level to the mouse MyEF3-like protein gene, which is identical with the mouse gene Edr (31,32). ORF2 is ϳ87% identical to the partial cDNA TRT1, a transcript from mink lung epithelial cells that is down-regulated after TGF-␤ treatment (33).…”
Section: Resultsmentioning
confidence: 87%
“…The highest homologies, 43 and 47%, respectively, were found to the retrotransposon element sushi of the pufferfish, Fugus rubripe. Further, ORF1 and ORF2 exhibited ϳ85% identity at the nucleotide level to the mouse MyEF3-like protein gene, which is identical with the mouse gene Edr (31,32). ORF2 is ϳ87% identical to the partial cDNA TRT1, a transcript from mink lung epithelial cells that is down-regulated after TGF-␤ treatment (33).…”
Section: Resultsmentioning
confidence: 87%
“…As many as nine clades (ancient phylogenetic groups of TEs, the origin of which can be traced back prior to vertebrates) of Ty3/Gypsy-like LTR retrotransposons are found in fish (Poulter and Butler, 1998;Volff et al, 2001bVolff et al, , 2003a, while none of them (with the exception of some domesticated sequences, Brandt et al, in press) are present in the genome of mouse and human. Other major groups of reverse transcriptase retrotransposons present in fish but with no functional equivalent in mammals include Ty1/Copia LTR retrotransposons , tyrosine recombinase-encoding retrotransposons Poulter, 2001, 2004), BEL-like LTR retrotransposons (Frame et al, 2001), Uri endonuclease-encoding Penelope-like elements (Lyozin et al, 2001;Volff et al, 2001a) and non-LTR retrotransposons with restriction enzyme-like endonuclease (Volff et al, 2001c;Bouneau et al, 2003). Even for non-LTR retrotransposons with apurinic-apyrimidinic endonuclease, which are extremely well represented in mouse and human genomes (Deininger et al, 2003;Kazazian, 2004), more clades are found in fish genomes (five) than in mammals (three) (Poulter et al, 1999;Volff et al, 1999Volff et al, , 2003a.…”
Section: Diversity Of Transposable Elements (Tes) In Fishmentioning
confidence: 99%
“…In contrast, despite a much higher global copy number of retroelements, only three families of retrotransposons are present in mammalian genomes: the non-LTR retrotransposons L1 (LINE1), L2 and L3/CR1. This suggests the elimination of several families of non-LTR retrotransposons with apurinic/apyrimidinic-like endonuclease (for example Rex1, Volff et al 2000) and restriction-like endonuclease (Rex6 and Zebulon; Volff et al 2001b, Penelopelike retrotransposons (Volff et al 2001a, Evgen'ev & Arkhipova 2005) and many families of LTR retrotransposons, particularly from the Ty3/gypsy type (Volff et al 2003). Even for transposable element families present in fish and mammals, fish genomes present a much higher diversity of ancient subfamilies compared with mammals, as reported for L1 (Furano et al 2004).…”
Section: Lineage-specific Extinction Of Transposable Elementsmentioning
confidence: 99%